Representations of pleasure and the female body in Marina Colasanti and Fabiana Faleiros - Marzani, Caroline (2024)
This article aims to reveal images of the female body and the issues related to the pleasure of women in poems by Marina Colasanti and Fabiana Faleiros. To this end, we use the Works Fino sangue (2005), by Marina Colasanti, and O pulso que cai e as tecnologias do toque (2016), by Fabiana Faleiros. Both poets bring the sensitive and erotic viewpoint (BATAILLE, 2017) about the act of masturbating, especially performed by women. Analyzing the history of sexuality (FOUCAULT, 2009; 2015) and gender and body (BUTLER, 2016; HARAWAY, 2009) and speaking place issues (DOLAR, 2015), we discuss the deconstruction of taboos about the female body.